CLONINIG AND EXPRESSION OF BAB-PATHOGENICITY ISLAND ANTIGENS FOR THE PRODUCTION OF VACCINE AGAINST HELICOBACTER PYLORI, THE RISK FACTOR FOR GASTRIC CANCER - Abbas Ghasemi, Seyed; Arjunan, Selvam; Senthil kumar, Radhakrishnan (Asian Journal of Pharmaceutical and Clinical Research, 2014)
BabA2, one of the two allele of BabA gene and a member protein of Helicobacter pylori, plays a vital role in assisting bacterial colonization in the stomach. However, its association with H pylori -related gastroduodenal diseases still remains unclear. In the present study, babA2 gene from Helicobacter pylori was amplified using specific primers and then cloned in pTZ57R/T and transformed into DH5-Î± cells successfully. Transformation was confirmed with plasmid extraction and followed by restriction digestion. IPTG was used as an inducer for the expression of babA2 protein and the protein was successfully isolated and quantified. The quantified protein was subjected to SDS PAGE to evaluate the expression of that protein. The sequence analysis have shown 99% perfectâ€ match with sequences of their corresponding gene (babA2) from GenBank as determined by using BLAST (version 2.7). Inserted babA2 gene was expressed significantly in the prokaryotic expression system, and specific strip at 75 KDa was demonstrated in SDS-PAGE. Further study is needed to substantiate that the expressed protein will act as an antigen for the humoral immunity against the Helicobacter pylori.Â